1976
DOI: 10.1002/jlac.197619760739
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoxyphenylverbindungen, VIII1) Borheterocyclen in der präparativen Naturstoffchemie; Synthese des Baeckeols2)

Abstract: 2,4,6‐Trimethoxytoluol gibt mit (CH3)2CH(CH)nCO2H (n = 0 oder 1) und Bortri‐ fluorid unter selektiver Entmethylierung stabile Borheterocyclen; deren Hydrolyse liefert Baeckeol (2a) sowie Homobaeckeol (2b). I,1,5‐Trimethoxybenzo1 wild doppelt acyliert, aber nur einfach entmethyliert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The analysis of the results showed that the highest yields were obtained with substrates bearing electron‐donating groups such as alkoxy substituents on the aromatic ring (Table 3, entries 6, 7 and 22‐2‐8). It is indeed gratifying to note that the reaction conditions are mild enough since they do not induce any dealkylation of an ether group located at an ortho position to the introduced acyl group (Table 3, entry 7) as observed in the acylation reaction with carboxylic acid catalyzed by BF 3 20…”
Section: Resultsmentioning
confidence: 96%
“…The analysis of the results showed that the highest yields were obtained with substrates bearing electron‐donating groups such as alkoxy substituents on the aromatic ring (Table 3, entries 6, 7 and 22‐2‐8). It is indeed gratifying to note that the reaction conditions are mild enough since they do not induce any dealkylation of an ether group located at an ortho position to the introduced acyl group (Table 3, entry 7) as observed in the acylation reaction with carboxylic acid catalyzed by BF 3 20…”
Section: Resultsmentioning
confidence: 96%
“…The reaction conditions are mild enough not to induce any dealkylation of an ether residue ortho to the introduced acyl group (Table 2, entry 11) as observed in the acylation reaction with carboxylic acid catalyzed by BF 3 . 3 Although the use of graphite for acylation of active aromatic compounds has been reported previously, 13 our new method, using a mixture of graphite and MeSO 3 H, offers significant improvements over the earlier method, reducing the reaction time considerably (20 minutes compared to eight hours), minimizing the amount of graphite from 1 g to 0.1 g, increasing the yield remarkably, and above all, using both electron donating and specially withdrawing substituted carboxylic acids instead of using the expensive and polluting acid halides that require special procedures in handling and working up.…”
Section: According Tomentioning
confidence: 99%
“…In order to minimize this problem, some catalytic Friedel-Crafts acylations have been developed recently. 2 In addition, acylations involving carboxylic acids and less toxic Lewis acids 3 or apparently non-hazardous acid catalysts 4 have been studied, although these procedures are not quite successful as practical and general synthetic methods. For instance, a methodology 4b of acylation of anisole with carboxylic acids over HZSM-5 zeolite, although environmentally safe, has limitations with regard to generality (no reaction with higher acids) and efficiency (reaction time of 48 h and concomitant Oacylation).…”
mentioning
confidence: 99%
“…32) [60]. Dealkylation of an ether residue ortho to the introduced acyl group is frequently encountered, as in the synthesis of baeckeol (Eq.…”
Section: Friedel-crafts Acylation Reactionsmentioning
confidence: 99%